Enhancement of the Antioxidant, Anti-Tyrosinase, and Anti-Hyaluronidase Activity of Morus alba L. Leaf extract by pulsed electric field extraction - Wantida Chaiyana (2020)
© 2020 by the authors. In this study we aimed to compare the chemical composition and biological activity between Morus alba L. leaf extract obtained with 95% v/v ethanol using a pulsed electric field (PEF) and the conventional maceration method. Extracts of M. alba leaves collected from Chiang Mai (CM), Sakon Nakon (SK), and Buriram (BR), Thailand, were investigated for 1-deoxynojirimycin content by high-performance liquid chromatography and for total phenolic content by the Folin–Ciocalteu method. Antioxidant activity was investigated by 2,20-diphenyl-1-picrylhydrazyl (DPPH), 2,2’-azinobis -3-ethylbenzothiazoline-6-sulphonate (ABTS), and ferric reducing antioxidant power (FRAP) assay. Anti-tyrosinase and anti-hyaluronidase activity was investigated by in vitro spectrophotometry. The results show that this is the first study to indicate PEF as a novel method for enhancing the phenolic content and antioxidant, anti-tyrosinase, and anti-hyaluronidase activity of M. alba leaf extract (P < 0.05). PEF extract of M. alba leaves collected from BR had comparable ABTS•+ scavenging activity to l-ascorbic acid and comparable anti-tyrosinase activity to kojic acid (P > 0.05). On the other hand, PEF extract of M. alba leaves collected from SK exhibited significantly high anti-hyaluronidase activity, comparable to that of oleanolic acid (P > 0.05). Therefore, PEF is suggested for further M. alba leaf extraction in the production of natural whitening and anti-aging cosmetic ingredients.